A Marriage Concept on Genesis 2:21-24 - Philip Suciadi Chia (Jurnal Didaskalia, 2019)
There are many discussions, OT exposition and Hebrew exegesis about marriage based on Genesis 2:21-24. It is interesting, however, to analyze how Latin Vulgate interprets and translates Genesis 2:21-24. Latin Vulgate seems to follow the word order of the Hebrew Bible and employ the literal translation of the Hebrew Bible. Although the translator uses the literal translation, he still has the freedom in his translation to accomplish his specific purposes such as the usage of ergo, cumque, replevit, virago and other words that will be discussed in this article. This research will be interpreted from the theme of unity, both man and woman.